Negative electrode active material, method for preparing negative electrode active material, negative electrode composition, negative electrode for lithium secondary battery comprising negative electrode composition, and lithium secondary battery comprising negative electrode

The chemical processing method is used to prepare the active material of the silicon system and controls its grain direction distribution, solve the problem of disconnecting the conductivity of the volume expansion of the volume expansion of the lithium secondary battery in the lithium secondary battery. The long life of the electrode.

CN119343785APending Publication Date: 2025-01-21LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380046140.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-31
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The volume expansion of silicon-based active materials during charging and discharging of lithium secondary batteries leads to disconnection of conductive paths, resulting in deterioration of battery performance. The prior art is difficult to effectively solve this problem.

Method used

The chemical processing method is used to prepare a silicon -based active material, controls its grain direction distribution, so that it can meet the specific crystal proportional formula, ensure that lithium ions are embedded and dewangled evenly, thereby reducing stress and extending the service life of the electrode.

Benefits of technology

The uniformity of lithium ion embedding and dehydration is realized, the phenomenon of silicon rupture is reduced, and the service life of the electrode and the performance stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343785A_ABST
    Figure CN119343785A_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode active material, a method for preparing the negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode composition, and a lithium secondary battery comprising the negative electrode. The negative electrode active material is a silicon-based active material, and contains a compound selected from the group consisting of SiOx (x = 0) and SiOx (0lt; xlt; according to the present invention, at least one of the groups (1, 2) is provided, and specific physical properties are satisfied, the reaction conditions in the chemical method are controlled to generate a silane gas, whereby the lithium intercalation / deintercalation reaction is uniform during charging and discharging, and the life retention rate of the active material is improved due to reduced stress thereto and less particle rupture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0110078 filed in the Korean Intellectual Property Office on August 31, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a negative electrode active material, a method for preparing the negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode composition, and a lithium secondary battery comprising the negative electrode. Background Art

[0003] As the use of fossil fuels is growing rapidly, there is an increasing demand for the use of alternative or clean energy, and as part of this trend, the most active research area is the field of power generation and storage using electrochemical reactions.

[0004] Currently, representative examples of electrochemical devices utilizing such electrochemical energy include secondary batteries, and their fields of use are increasingly expanding.

[0005] With the increase of technology development and demand for mobile devices, the demand for secondary batteries as energy sources is growing rapidly. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as an electrode for such a high-capacity lithium secondary battery, research on the preparation method of a high-density electrode with higher energy density per unit volume has been actively carried out.

[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material for inserting and extracting lithium ions from the positive electrode, and as the negative electrode active material, silicon-based particles having a high discharge capacity can be used.

[0007] In particular, with the recent increase in demand for high-density energy batteries, research has been actively conducted on methods of increasing capacity by using silicon-based compounds such as Si / C or SiOx, which have a capacity 10 times or more than that of graphite-based materials, as negative electrode active materials. Although silicon-based compounds as high-capacity materials have a higher capacity than graphite used in the related art, there is a problem that the volume expands rapidly during charging, disconnecting the conductive path, thereby causing deterioration of battery characteristics.

[0008] Therefore, in order to solve the problems when silicon-based compounds are used as negative electrode active materials, measures for adjusting the driving potential have been discussed; and measures for suppressing volume expansion itself, such as methods of further coating the active material layer with a thin film and methods of adjusting the particle size of silicon-based compounds; various measures for preventing disconnection of the conduction path, etc., but due to the performance of the battery may deteriorate instead, the application of these measures has limitations; there are limitations in applying the methods, which still results in limitations in the commercialization of the preparation of batteries with a negative electrode having a high content of silicon-based compounds.

[0009] Therefore, even when using a silicon-based active material as the negative electrode active material to improve the capacity performance, it is necessary to study the silicon-based active material itself that can alleviate the silicon cracking phenomenon caused by the insertion and extraction of lithium during the charge and discharge process.

[0010] <Related Technical Documents>

[0011] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the Invention

[0012] Technical issues

[0013] When preparing a silicon-based active material using a chemical processing method instead of the existing pulverization processing method, the physical properties of the silicon-based active material itself can be adjusted, so it is confirmed that during the lithium insertion / extraction reaction process, the reaction occurs uniformly and the stress applied to the silicon-based active material is reduced. In addition, through research, it is confirmed that when preparing a silicon-based active material by a chemical processing method, the grain orientation distribution of the silicon-based active material itself can be controlled, and the insertion and extraction of lithium ions can be carried out uniformly by controlling the grain orientation.

[0014] Therefore, the present application relates to a negative electrode active material, a method for preparing a negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery containing the negative electrode composition, and a lithium secondary battery containing the negative electrode, which can solve the above problems.

[0015] Technical Solution

[0016] An exemplary embodiment of the present specification provides a negative electrode active material containing a silicon-based active material including (220) crystal planes and (111) crystal planes, wherein the silicon-based active material satisfies the following Formula 1, includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 70 parts by weight or more.

[0017] [Formula 1]

[0018] 45 ≤ (X / Y) × 100

[0019] In Formula 1,

[0020] Y represents the proportion of the (111) crystal plane in the silicon-based active material,

[0021] X represents the proportion of the (220) crystal plane in the silicon-based active material.

[0022] Another exemplary embodiment provides a method for preparing a negative electrode active material according to the present application, the method comprising: depositing a silicon-based active material on the surface of a crystal nucleus by subjecting a silane gas to a chemical reaction; and obtaining the silicon-based active material deposited on the surface of the crystal nucleus, wherein the silicon-based active material satisfies Formula 1.

[0023] Another exemplary embodiment aims to provide a negative electrode composition, the negative electrode composition comprising: a negative electrode active material according to the present application; a negative electrode conductive material; and a negative electrode binder.

[0024] Another exemplary embodiment aims to provide a negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: a negative electrode current collector layer; and a negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer comprises the negative electrode composition according to the present application or a cured product thereof.

[0025] Finally, a lithium secondary battery is provided, the lithium secondary battery comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.

[0026] Beneficial Effects

[0027] The negative electrode active material of the present invention comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2) as the silicon-based active material, and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 70 parts by weight or more, that is, it has a pure Si active material. At the same time, different from the existing pulverization processing method, it is manufactured by controlling the reaction conditions of a chemical method (silane gas). Therefore, the negative electrode active material of the present invention comprises a silicon-based active material that satisfies predetermined physical properties. When the silicon-based active material prepared as described above is used, the lithium insertion and extraction reactions during the charge and discharge process can proceed uniformly, and the stress applied to the silicon-based active material can be reduced to alleviate particle breakage, thereby improving the service life retention rate of the electrode.

[0028] In particular, the present application is characterized in that, when the silicon-based active material is prepared as described above, the grain direction distribution is controlled to satisfy the range of the above formula 1. That is, when a relatively large proportion of (111) crystal planes are formed as in the related art, the lithium mobility of the (111) crystal planes is lower than that of the (220) crystal planes, so that lithium cannot enter and exit uniformly during the lithium insertion / deinsertion reaction. However, unlike in the related art, the silicon-based active material according to the present application contains a large proportion of (220) crystal planes, which allows lithium to enter and exit uniformly during the lithium insertion / deinsertion reaction, thereby reducing the silicon cracking phenomenon on the electrode surface. Therefore, the silicon-based active material is characterized in that the service life characteristics of the electrode are enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a diagram showing a stack structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.

[0030] Figure 2 is a diagram illustrating a stack structure of a lithium secondary battery according to an exemplary embodiment of the present application.

[0031] Figure 3 It is a diagram showing a method of calculating the grain size.

[0032] Figure 4 is a diagram showing a unit cell structure of a silicon-based active material according to the present application.

[0033] Figure 5 is a diagram showing the (220) plane and the (111) plane of the silicon-based active material according to the present application.

[0034] Figure 6 This is a diagram comparing the densities of the (220) plane and the (111) plane of a silicon-based active material.

[0035] <Description of Reference Numerals and Symbols>

[0036] 10: Negative electrode collector layer

[0037] 20: Negative electrode active material layer

[0038] 30: Diaphragm

[0039] 40: Positive electrode active material layer

[0040] 50: Positive electrode collector layer

[0041] 100: Negative electrode for lithium secondary battery

[0042] 200: Positive electrode for lithium secondary battery DETAILED DESCRIPTION

[0043] Before describing the present invention, some terms will first be defined.

[0044] In the present specification, when a part “comprises” one constituent element, unless otherwise specifically described, this does not mean excluding other constituent elements but means that other constituent elements may further be included.

[0045] In the present specification, 'p to q' means a range of 'p or more and q or less'.

[0046] In this specification, "specific surface area" is measured by the BET method, specifically, calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77 K) using BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the measurement method.

[0047] In this specification, "Dn" means particle size distribution, and means the particle size at n% point according to the cumulative distribution of the number of particles of particle size. That is, D50 is the particle size (average particle size) at 50% point according to the cumulative distribution of the number of particles of particle size, D90 is the particle size at 90% point according to the cumulative distribution of the number of particles of particle size, and D10 is the particle size at 10% point according to the cumulative distribution of the number of particles of particle size. On the other hand, the average particle size can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the obtained dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the difference in the diffraction pattern according to the particle size when the particle passes through the laser beam to calculate the particle size distribution.

[0048] In an exemplary embodiment of the present application, the particle size or particle diameter may mean an average diameter or a representative diameter of each particle forming the metal powder.

[0049] In the present specification, the fact that a polymer includes a monomer as a monomer unit means that the monomer participates in a polymerization reaction and is thus included in the polymer as a repeating unit. In the present specification, when a polymer includes a monomer, it is interpreted as the same as when the polymer includes a monomer as a monomer unit.

[0050] In this specification, 'polymer' is to be understood as being used in a broad sense, including copolymers, unless otherwise specified as a 'homopolymer'.

[0051] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene conversion molecular weights measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise described, molecular weight means weight average molecular weight.

[0052] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings so that those of ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, the present invention can be implemented in various different forms and is not limited to the following description.

[0053] An exemplary embodiment of the present specification provides a negative electrode active material including a silicon-based active material including (220) crystal planes and (111) crystal planes, where the silicon-based active material satisfies the following Formula 1, the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 70 parts by weight or more.

[0054] [Formula 1]

[0055] 45 ≤ (X / Y) × 100

[0056] In Formula 1,

[0057] Y means the proportion of (111) crystal planes in the silicon-based active material.

[0058] X means the proportion of (220) crystal planes in the silicon-based active material.

[0059] The present application is characterized in that when preparing the silicon-based active material, the grain orientation distribution is controlled to satisfy the range of the above Formula 1. That is, when a relatively large proportion of (111) crystal planes are formed as in the related art, the lithium mobility of the (111) crystal plane is lower than that of the (220) crystal plane, so that during the lithium insertion / extraction reaction process, lithium cannot enter and exit uniformly. However, different from the related art, the silicon-based active material according to the present application includes a large proportion of (220) crystal planes, which enables lithium to enter and exit uniformly during the lithium insertion / extraction reaction process. Therefore, the phenomenon of silicon cracking on the electrode surface can be alleviated. Therefore, the silicon-based active material is characterized by enhancing the service life characteristics of the electrode.

[0060] Figure 4 Illustrated is the unit cell structure of the silicon-based active material according to the present application. The silicon-based active material includes crystal planes. Specifically, in Figure 5 it is possible to confirm the (220) plane and the (111) plane of the silicon-based active material. Figure 6 Corresponds to a graph comparing the densities of the (220) plane and the (111) plane of the silicon-based active material. As can be specifically confirmed, it can be confirmed that when confirming the density and direction of the (220) plane as well as the (110) plane, since the particle density in the same area on the 220 plane is lower, when Li moves, the (220) plane with a smaller particle density is more favorable.

[0061] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the silicon-based active material comprises one or more selected from the group consisting of spherical silicon-based active materials and plate-like silicon-based active materials, and the content of the spherical silicon-based active material is 80 parts by weight or more based on 100 parts by weight of the silicon-based active material.

[0062] In another exemplary embodiment, the silicon-based active material comprises one or more selected from the group consisting of spherical silicon-based active materials and plate-like silicon-based active materials, and the content of the spherical silicon-based active material may be 80 parts by weight or more, 85 parts by weight or more, or 90 parts by weight or more, and may be 100 parts by weight or less, 99 parts by weight or less, or 95 parts by weight or less, based on 100 parts by weight of the silicon-based active material.

[0063] In the present application, the plate-like silicon-based active material may refer to a silicon-based active material having a well-developed (111) crystal plane and having a wide surface shape instead of a spherical shape, and the spherical silicon-based active material may refer to a silicon-based active material having a more developed (220) crystal plane than the plate-like silicon-based active material and therefore having spherical particles instead of a wide spread surface shape.

[0064] That is, the silicon-based active material may have a spherical form, and the roundness thereof is, for example, 0.8 or more, for example, 0.8 to 0.95, for example, 0.9 to 0.95, for example, 0.93 to 0.95.

[0065] In the present application, the spherical silicon-based active material means an active material having a particle roundness of 0.9 or more when measured, and an active material having a roundness less than 0.9 can be classified as a plate-like active material.

[0066] In the present application, the circularity is determined by the following Formula 2, where A is the area and P is the boundary line.

[0067] [Formula 2]

[0068] 4πA / P 2

[0069] Specifically, the circularity can be expressed by the formula 2-1 described below. The circularity can also be expressed by the formula [4π*actual area of ​​silicon-based active material / (boundary) 2 ] to indicate.

[0070] In an exemplary embodiment of the present application, the above X means the ratio of the (220) crystal plane in the silicon-based active material, and means the ratio based on the entire surface of the silicon-based active material, and the above X may satisfy 30 to 60, preferably 35 to 60, and more preferably 35 to 55.

[0071] In an exemplary embodiment of the present application, the above-mentioned Y refers to the proportion of the (111) crystal plane in the silicon-based active material, and refers to the proportion based on the entire surface of the silicon-based active material. The above-mentioned Y may satisfy 50 to 80, preferably 55 to 80, more preferably 55 to 75.

[0072] In an exemplary embodiment of the present application, the silicon-based active material may further include various crystal planes.

[0073] In an exemplary embodiment of the present application, the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2). Based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more.

[0074] In an exemplary embodiment of the present application, the silicon-based active material includes SiOx (x = 0). Based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more.

[0075] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and the content may be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.

[0076] In an exemplary embodiment of the present application, a silicon-based active material including pure silicon (Si) particles may be particularly used as the silicon-based active material. Using pure silicon (Si) particles as the silicon-based active material may mean that, based on a total of 100 parts by weight of the silicon-based active material, the above range includes pure Si particles (SiOx (x = 0)) not combined with other particles or elements.

[0077] In an exemplary embodiment of the present application, the silicon-based active material may be composed of silicon-based particles having 100 parts by weight of SiOx (x = 0) based on 100 parts by weight of the silicon-based active material.

[0078] In an exemplary embodiment of the present application, the silicon-based active material may include metal impurities. In this case, the impurities are metals that may generally be included in the silicon-based active material. Based on 100 parts by weight of the silicon-based active material, the specific content may be 0.1 part by weight or less.

[0079] Since silicon-based active materials have significantly higher capacity than graphite-based active materials used in related arts, attempts to apply silicon-based active materials are increasing, but since silicon-based active materials have a high volume expansion rate during charge and discharge, the attempts are limited to the case where a small amount of silicon-based active materials is mixed with a graphite-based active material.

[0080] Therefore, the present invention solves the above-mentioned problems by adjusting the grain size or specific surface area of ​​the silicon-based active material itself instead of adjusting the composition of the conductive material and the binder while improving the capacity performance by using only the silicon-based active material as the negative electrode active material.

[0081] In an exemplary embodiment of the present application, the grain size of the silicon-based active material may be 200 nm or less.

[0082] In another exemplary embodiment, the grain size of the silicon-based active material may be 200 nm or less, preferably 130 nm or less, more preferably 120 nm or less, even more preferably 100 nm or less, specifically 95 nm or less, more specifically 91 nm or less. The grain size range of the silicon-based active material may be 10 nm or more, preferably 15 nm or more.

[0083] The silicon-based active material has the above-mentioned grain size, and the grain size of the silicon-based active material can be adjusted by changing the process conditions in the preparation process. In this case, by satisfying the above-mentioned range, the grain boundary distribution is wide, so that during the lithium ion embedding process, the lithium ions can enter evenly, thereby reducing the stress applied when the lithium ions are embedded in the silicon particles, thereby reducing the particle breakage. As a result, the silicon-based active material is characterized in that it can improve the service life stability of the negative electrode. When the grain size exceeds the above-mentioned range, the grain boundary distribution in the particles is narrow. In this case, the lithium ions are unevenly embedded in the particles, so that the particles break due to the large stress caused by the ion embedding.

[0084] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the silicon-based active material includes a crystal structure having a grain distribution of 1 nm or more and 200 nm or less, and the area ratio of the crystal structure is 5% or less based on the total area of ​​the silicon-based active material.

[0085] In another exemplary embodiment, the area ratio of the crystalline structure may be 5% or less or 3% or less, and may be 0.1% or more, based on the total area of ​​the silicon-based active material.

[0086] That is, the grain size of the silicon-based active material according to the present application is 200 nm or less, and the size of each crystal structure is small, which can satisfy the above area ratio. Therefore, the distribution of the grain boundaries can be widened, and thus the above effect can be exhibited.

[0087] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the number of crystal structures included in the silicon-based active material is 20 or more.

[0088] In another exemplary embodiment, the number of crystal structures included in the silicon-based active material may be 20 or more, 30 or more, or 35 or more, and may satisfy a range of 60 or less or 50 or less.

[0089] That is, as described above, when the grain size satisfies the above range and the number of crystal structures also satisfies the above range, the strength of the silicon-based active material itself has an appropriate range, so that the silicon-based active material has the characteristic of being able to impart flexibility when contained in an electrode, and also has the characteristic of being able to effectively suppress volume expansion.

[0090] In the present application, a grain means a crystal particle in a metal or material, which is a collection of irregular shapes of microscopic size, and a grain size may mean the diameter of an observed grain particle. That is, in the present application, a grain size means the size of a domain that shares the same crystal orientation in a particle, and has a different concept from a particle size or a particle size that indicates a material size.

[0091] In an exemplary embodiment of the present application, the grain size can be calculated as a full width at half maximum (FWHM) value by XRD analysis. Specifically, Figure 3 The method for calculating the grain size is shown in Figure 3 In the above, the remaining values ​​except L are measured by XRD analysis of the silicon-based active material, and the grain size can be measured by the Debey-Scherrer formula indicating that FWHM is inversely proportional to the grain size. In this case, the Debey-Scherrer formula is the same as the following formula 1-1.

[0092] [Formula 1-1]

[0093] FWHM=Kλ / LCosθ

[0094] In formula 1-1,

[0095] L is the grain size, K is a constant, θ is the Bragg angle, and λ refers to the wavelength of the X-ray.

[0096] Furthermore, the shapes of the crystal grains are various, and thus three-dimensional measurement can be performed. The crystal grain size can generally be measured by a commonly used circle method and diameter measurement method, but the present invention is not limited thereto.

[0097] The diameter measurement method can be performed by drawing 5 to 10 equilibrium lines each having a length of L mm on a micrograph of the particle to be measured, counting the number of grains z on the line, and averaging the number of grains z. In this case, only those grains that enter completely are counted, while those that cross the line are excluded. When the number of lines is defined as P and the magnification is defined as V, the average particle diameter can be calculated using the following formula 1-2.

[0098] [Formula 1-2]

[0099] Dm = (L*P*10 3 ) / (zV) (μm)

[0100] In addition, in the circle method, the average particle area can be calculated using the following formula 1-3 by drawing a circle of a predetermined diameter on a micrograph of the target particle, and then using the number of grains entering the circle and the number of grains on the boundary line to obtain the average area of ​​the grains.

[0101] [Formula 1-3]

[0102] Fm = (Fk * 10 6 ) / ((0.67n + z) V 2 )( μm 2 )

[0103] In Formula 1-3, Fm means the average particle area, Fk means the measurement area on the photograph, z means the number of particles entering the circle, n means the number of particles on the arc, and V means the magnification of the microscope.

[0104] In an exemplary embodiment of the present application, the negative electrode active material may include a specific surface area of ​​0.25 m 2 / g or more silicon-based active material.

[0105] In another exemplary embodiment, the specific surface area of ​​the silicon-based active material may be 0.25 m 2 / g or more, preferably 0.28 m 2 / g or more, more preferably 0.30 m 2 / g or more, specifically 0.31 m 2 / g or more, more specifically 0.32 m 2 / g or more. The specific surface area of ​​the silicon-based active material can meet 3 m 2 / g or less, preferably 2.5 m 2 / g or less, more preferably 2.2m 2 The specific surface area can be measured according to DIN 66131 (using nitrogen).

[0106] The silicon-based active material has the above-mentioned specific surface area, and the size of the specific surface area of ​​the silicon-based active material can be adjusted by changing the process conditions in the preparation process described below and the growth conditions of the silicon-based active material. That is, when the negative electrode active material is prepared using the preparation method according to the present application, the negative electrode active material has a larger specific surface area than particles with the same particle size due to the rough surface. In this case, since the bonding strength with the binder is increased by satisfying the above-mentioned range, the negative electrode active material is characterized in that it can reduce electrode cracking caused by repeated charge and discharge cycles.

[0107] In addition, during the lithium ion embedding process, lithium ions can be uniformly entered, thereby reducing the stress applied when lithium ions are embedded in silicon particles, thereby alleviating particle rupture. As a result, the negative electrode is characterized in that the service life stability of the negative electrode can be improved. When the specific surface area size is smaller than the above range, the surface is smoothly formed even when the particles have the same particle size, the bonding strength with the binder deteriorates, and the electrode rupture occurs, and in this case, lithium ions are unevenly embedded in the particles, so that the particle rupture occurs due to the large stress caused by ion embedding.

[0108] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the silicon-based active material satisfies the range of the following formula 2-1.

[0109] [Formula 2-1]

[0110] X1 / Y1 ≤ 0.960

[0111] In formula 2-1,

[0112] X1 is the actual area of ​​the silicon-based active material,

[0113] Y1 means the area of ​​a spherical particle having the same perimeter as the silicon-based active material.

[0114] The measurement of formula 2-1 can be performed using a particle image analyzer. Specifically, after the silicon-based active material according to the present application is spread on a glass plate by air jet, a shadow image of the spread silicon-based active material particles can be taken to determine the shape of 10,000 silicon-based active material particles in the photograph. In this case, formula 2-1 is a value representing the average value of 10,000 particles. Formula 2-1 according to the present application can be measured by the above image, and the above formula 2-1 can be represented by the roundness of the silicon-based active material. The roundness can also be expressed by the formula [4π*actual area of ​​the silicon-based active material / (boundary) 2 ] to indicate.

[0115] In an exemplary embodiment of the present application, the circularity of the silicon-based active material may be, for example, 0.960 or less, for example, 0.957 or less. The circularity of the silicon-based active material may be 0.8 or more, for example, 0.9 or more, specifically 0.93 or more, more specifically 0.94 or more, for example, 0.941 or more.

[0116] In an exemplary embodiment of the present application, a negative electrode active material is provided, wherein the silicon-based active material satisfies the range of the following formula 2-2.

[0117] [Formula 2-2]

[0118] X2 / Y2 ≤ 0.995

[0119] In formula 2-2,

[0120] Y2 is the actual circumference of the silicon-based active material,

[0121] X2 is the perimeter of the circumscribed pattern of the silicon-based active material.

[0122] The measurement of formula 2-2 can be performed using a particle image analyzer. Specifically, after the silicon-based active material according to the present application is spread on a glass plate by air jet, a shadow image of the spread silicon-based active material particles can be taken to determine the shape of 10,000 silicon-based active material particles in the photograph. In this case, formula 2-2 is a value representing the average value of 10,000 particles. Formula 2-2 according to the present application can be measured by the above image, and the above formula 2-2 can be represented by the convexity of the silicon-based active material.

[0123] In an exemplary embodiment of the present application, X2 and Y2 may satisfy the range of X2 / Y2≤0.996, preferably the range of X2 / Y2≤0.995, and X2 and Y2 may satisfy the range of 0.8≤X2 / Y2, preferably 0.9≤X2 / Y2, more preferably 0.95≤X2 / Y2, specifically 0.98≤X2 / Y2.

[0124] This may mean that the smaller the value of the above formula 2-1 or 2-2, the greater the roughness of the silicon-based active material may be. When a silicon-based active material having the above range is used, the silicon-based active material is characterized in that the bonding strength with the binder is increased, thereby being able to reduce electrode cracking caused by repeated charge and discharge cycles.

[0125] In an exemplary embodiment of the present application, the silicon-based active material may include silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less.

[0126] The fact that the silicon-based active material contains silicon-based particles having a particle size distribution of 0.01 μm or more and 30 μm or less means that a large number of individual silicon-based particles having a particle size within the above range are contained, and the number of silicon-based particles contained is not limited.

[0127] When the silicon-based particles have a spherical shape, the particle size of the silicon-based particles can be expressed as the diameter of the silicon-based particles, but even in the case of other non-spherical shapes, the particle size can be measured by comparison with the case of the spherical shape. Generally, the particle size of individual silicon-based particles can be measured by measurement methods in the art.

[0128] On the other hand, the average particle size (D50 particle size) of the silicon-based active material of the present invention can be 3 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is included in the above range, since the specific surface area of ​​the particles is included in a suitable range, the viscosity of the negative electrode slurry is formed in a suitable range. Therefore, the dispersion of the particles constituting the negative electrode slurry is promoted. In addition, the size of the silicon-based active material has a value equal to or greater than the lower limit value range, and since the composite composed of the conductive material and the binder in the negative electrode slurry makes the contact area between the silicon particles and the conductive material excellent, the possibility of the conductive network being continuous is increased, thereby improving the capacity retention rate. On the other hand, when the average particle size satisfies the above range, excessively large silicon particles are eliminated to form a smooth negative electrode surface, so that the phenomenon of uneven current density during charge and discharge can be prevented.

[0129] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of ​​the silicon-based active material is preferably 0.01 to 150.0 m 2 / g, more preferably 0.1 to 100.0 m 2 / g, particularly preferably 0.2 to 80.0 m 2 / g, most preferably 0.2 to 18.0 m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen).

[0130] In an exemplary embodiment of the present application, a negative electrode composition is provided, the negative electrode composition including: the negative electrode active material; a negative electrode conductive material; and a negative electrode binder.

[0131] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the content of the silicon-based active material is 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.

[0132] In another exemplary embodiment, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, based on 100 parts by weight of the negative electrode composition, and the content thereof may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less.

[0133] The negative electrode composition according to the present application is characterized in that even if a silicon-based active material having a significantly high capacity is used within the above-mentioned range, by using a negative electrode active material that satisfies a specific grain size and can suppress the volume expansion rate during charge and discharge, even if the silicon-based active material is included in the above-mentioned range, the performance of the negative electrode will not deteriorate, and the output characteristics during charge and discharge are also excellent.

[0134] In the related art, only graphite compounds are usually used as negative electrode active materials, but recently, as the demand for high-capacity batteries increases, attempts to mix and use silicon-based active materials in order to increase capacity are increasing. However, in the case of silicon-based active materials, even if the properties of the silicon-based active materials themselves are adjusted as described above, the volume expands rapidly during the charge and discharge process, so that in some cases, the conductive path formed in the negative electrode active material layer may be damaged.

[0135] Therefore, in an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a planar conductive material, and a linear conductive material.

[0136] In an exemplary embodiment of the present application, the point-shaped conductive material can be used to enhance the conductivity of the negative electrode, and means a point-shaped or spherical conductive material having conductivity without causing chemical changes. Specifically, the point-shaped conductive material can be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and in terms of achieving high conductivity and excellent dispersibility, carbon black can be preferably included.

[0137] In an exemplary embodiment of the present application, the BET specific surface area of ​​the dot-shaped conductive material may be 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less, more preferably 50 m 2 / g or more and 60 m 2 / g or less.

[0138] In an exemplary embodiment of the present application, the functional group content (volatile matter) of the dot-shaped conductive material may satisfy 0.01% to 1%, preferably 0.01% to 0.3%, and more preferably 0.01% to 0.1%.

[0139] In particular, when the functional group content of the dot-shaped conductive material satisfies the above range, there are functional groups located on the surface of the dot-shaped conductive material, so that when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent. In particular, in the present invention, since a specific silicon-based active material is used, the functional group content of the dot-shaped conductive material can be reduced, and therefore, the present invention has an excellent effect in improving dispersibility.

[0140] In an exemplary embodiment of the present application, it is characterized in that the dot-shaped conductive material having a functional group content within the above range is included together with the silicon-based active material, and the functional group content can be adjusted according to the degree of heat treatment of the dot-shaped conductive material.

[0141] In an exemplary embodiment of the present application, the dot-shaped conductive material may have a particle size of 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.

[0142] In an exemplary embodiment of the present application, the conductive material may include a planar conductive material.

[0143] The planar conductive material can be used to improve conductivity by increasing surface contact between silicon particles in the negative electrode while suppressing disconnection of the conductive path due to volume expansion. The planar conductive material can be in the form of a plate-like conductive material or a bulk conductive material.

[0144] In an exemplary embodiment of the present application, the planar conductive material may include at least one selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.

[0145] In an exemplary embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 3.5 μm to 5 μm. When the average particle size satisfies the above range, sufficient particle size promotes dispersion without causing excessive increase in viscosity of the negative electrode slurry. Therefore, when the particles are dispersed using the same equipment and time, the dispersion effect is excellent.

[0146] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the planar conductive material has a D10 of 0.5 μm to 2.0 μm, a D50 of 2.5 μm to 3.5 μm, and a D90 of 6.5 μm to 15.0 μm.

[0147] In an exemplary embodiment of the present application, as the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area; or a low specific surface area planar conductive material may be used.

[0148] In an exemplary embodiment of the present application, as the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without restriction, but in particular, the planar conductive material according to the present application may be affected to a certain extent by the dispersion effect in terms of electrode performance, so it may be particularly desirable to use a planar conductive material with a low specific surface area that does not cause dispersion problems.

[0149] In an exemplary embodiment of the present application, the BET specific surface area of ​​the planar conductive material may be 1 m 2 / g or above.

[0150] In another exemplary embodiment, the BET specific surface area of ​​the planar conductive material may be 1 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m 2 / g and above 250 m 2 / g or less.

[0151] As the planar conductive material according to the present application, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used.

[0152] In another exemplary embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 300 m 2 / g or less.

[0153] In another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g and above 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.

[0154] As other conductive materials, there may be linear conductive materials, such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term 'bundle-type' used herein refers to a secondary shape in the form of a bundle or rope, in which a plurality of carbon nanotube units are aligned or wound side by side in an alignment in which the longitudinal axes of the carbon nanotube units are substantially the same. In the carbon nanotube unit, the graphite sheet has a cylindrical shape with a nanometer-sized diameter and has an sp2 bond structure. In this case, depending on the angle and structure of the curling of the graphite sheet, the carbon nanotube unit may exhibit the characteristics of a conductor or a semiconductor. Compared with entangled type carbon nanotubes, the bundle-type carbon nanotubes can be uniformly dispersed during the preparation of the negative electrode, and the conductivity of the negative electrode can be improved by smoothly forming a conductive network in the negative electrode.

[0155] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the content of the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode composition.

[0156] In another exemplary embodiment, the content of the negative electrode conductive material may be 0.1 parts by weight or more and 40 parts by weight or less, preferably 0.2 parts by weight or more and 30 parts by weight or less, more preferably 0.4 parts by weight or more and 25 parts by weight or less, and most preferably 0.4 parts by weight or more and 10 parts by weight or less, based on 100 parts by weight of the negative electrode composition.

[0157] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the negative electrode conductive material comprises a planar conductive material and a linear conductive material.

[0158] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the negative electrode conductive material comprises a planar conductive material and a linear conductive material, and their contents are 80 parts by weight or more and 99.9 parts by weight or less and 0.1 parts by weight or more and 20 parts by weight or less, respectively, based on 100 parts by weight of the negative electrode conductive material.

[0159] In another exemplary embodiment, the content of the planar conductive material in the negative electrode conductive material may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 85 parts by weight or more and 99.9 parts by weight or less, and more preferably 95 parts by weight or more and 98 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.

[0160] In another exemplary embodiment, the content of the linear conductive material in the negative electrode conductive material may be 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.1 parts by weight or more and 15 parts by weight or less, and more preferably 0.2 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.

[0161] In an exemplary embodiment of the present application, since the negative electrode conductive material includes a planar conductive material and a linear conductive material, and the planar conductive material and the linear conductive material each satisfy the composition and proportion, the negative electrode conductive material has the following characteristics: it does not significantly affect the service life characteristics of existing lithium secondary batteries, and in particular, when it includes a planar conductive material and a linear conductive material, the sites at which the battery can be charged and discharged are increased, so the output characteristics at a high C rate are excellent and the amount of high-temperature gas generated is reduced.

[0162] In an exemplary embodiment of the present application, the negative electrode conductive material may be composed of a linear conductive material.

[0163] In particular, when a linear conductive material is used alone, the electrode structure can be improved because the electrode tortuosity, which is a problem of silicon-based negative electrodes, can be simplified. Accordingly, the negative electrode conductive material is characterized by being able to reduce resistance to lithium ion movement in the electrode.

[0164] In an exemplary embodiment of the present application, when the negative electrode conductive material contains only linear conductive material, the content of the negative electrode conductive material may be 0.1 parts by weight or more and 5 parts by weight or less, preferably 0.2 parts by weight or more and 3 parts by weight or less, and more preferably 0.4 parts by weight or more and 1 part by weight or less, based on 100 parts by weight of the negative electrode composition.

[0165] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material used for the positive electrode. That is, the first negative electrode conductive material according to the present application is used to capture the contact sites between the silicon-based active materials in which the electrode volume expands greatly due to charge and discharge, while the positive electrode conductive material is used to play a buffering role as a buffer during rolling and to impart a part of conductivity, and its structure and function are completely different from those of the negative electrode conductive material of the present invention.

[0166] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different structure from the conductive material applied to the graphite-based active material. That is, the conductive material used for the electrode with the graphite-based active material simply has particles smaller than the active material, and thus has the characteristics of enhancing the output characteristics and imparting a part of the conductivity, and its structure and function are completely different from the negative electrode conductive material applied together with the silicon-based active material in the present invention.

[0167] In an exemplary embodiment of the present application, the planar conductive material used as the above-mentioned negative electrode conductive material has a different structure and function from the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and means a material processed into a spherical or dot-like shape and used to promote lithium ion storage and release.

[0168] In contrast, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and may be in the form of plate-like graphite. That is, the plate-like conductive material is a material contained in order to maintain a conductive path in the negative electrode active material layer, and means a material for ensuring a conductive path in a planar form in the negative electrode active material layer rather than playing a role in storing and releasing lithium.

[0169] That is, in the present application, the fact that plate-like graphite is used as a conductive material means that the plate-like graphite is processed into a planar or plate-like shape and used as a material that ensures a conductive path rather than a material that functions to store or release lithium. In this case, the negative electrode active material contained together has a high capacity characteristic for lithium storage and release, and functions to be able to store and release all lithium ions transferred from the positive electrode.

[0170] In contrast, in the present application, the fact that a carbon-based active material is used as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.

[0171] That is, in one exemplary embodiment of the present application, artificial graphite or natural graphite as a carbon-based active material is in a dot-like form, and its BET specific surface area may satisfy 0.1 m 2 / g or more and 4.5 m 2In addition, the plate-like graphite as a planar conductive material is in a planar form, and its BET specific surface area can be 5 m 2 / g or above.

[0172] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0173] The negative electrode binder according to an exemplary embodiment of the present application plays a role in supporting the active material and the conductive material during the volume expansion and relaxation of the silicon-based active material, thereby preventing the distortion and structural deformation of the negative electrode structure. When the above-mentioned effects are met, all common binders can be applied, specifically, aqueous binders can be used, and more specifically, PAM-based binders can be used.

[0174] In an exemplary embodiment of the present application, based on 100 parts by weight of the negative electrode composition, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, and more preferably 20 parts by weight or less, and its content may be 5 parts by weight or more, 10 parts by weight or more.

[0175] An exemplary embodiment of the present application provides a method for preparing a negative electrode active material according to the present application, the method comprising: depositing a silicon-based active material onto a crystal core surface by chemically reacting silane gas; and obtaining the silicon-based active material deposited onto the crystal core surface, wherein the silicon-based active material satisfies the following formula 1.

[0176] [Formula 1]

[0177] 45 ≤ (X / Y) × 100

[0178] In formula 1,

[0179] Y means the ratio of (111) crystal planes in the silicon-based active material,

[0180] X means the ratio of (220) crystal planes in the silicon-based active material.

[0181] According to an example, the silane gas may include one or more gases selected from monosilane, dichlorosilane and trichlorosilane, and may specifically be trichlorosilane gas.

[0182] In the present application, a method for preparing a negative electrode active material is provided, wherein the deposition of a silicon-based active material onto a surface of a crystal core by chemically reacting silane gas is performed under a high temperature condition of 100° C. or above.

[0183] In an exemplary embodiment of the present application, the deposition of silicon-based active materials onto the surface of the crystal nucleus by chemically reacting silane gas can be performed under a pressure condition of 10 Pa to 150 Pa. The above low pressure can reduce the silicon growth rate, thereby achieving the formation of small grains. The step can be performed at a temperature of 100°C or above, specifically above 500°C, preferably above 800°C, more preferably 800°C to 1300°C or 800°C to 2200°C. This is lower than the temperature in the existing gas atomization method of heating Si to above 1600°C to melt Si.

[0184] In an exemplary embodiment of the present application, the step may further include: depositing the silicon-based active material onto the surface of the crystal core by chemically reacting silane gas; and then growing the silicon-based active material by crystal nucleation.

[0185] In this case, the growth of the silicon-based active material by crystal nucleation can be performed under a temperature condition of 800° C. or more, preferably 800° C. to 1300° C. This is lower than the temperature in the existing gas atomization method in which Si is heated to 1600° C. or more to melt Si. In addition, the growth of the silicon-based active material by crystal nucleation can be performed under a pressure of 100 Pa to 150 Pa. The above low pressure can reduce the silicon growth rate, thereby achieving the formation of small grains and a specific specific surface area.

[0186] In an exemplary embodiment of the present application, a method for preparing a negative electrode active material is provided, the method further comprising: depositing a silicon-based active material onto a surface of a crystal nucleus by chemically reacting silane gas; and subsequently growing the silicon-based active material by crystal nucleation, wherein growing the silicon-based active material by crystal nucleation comprises generating crystal nuclei at a temperature above 800°C for 1 hour to 24 hours.

[0187] By the above-described preparation method, a silicon-based active material in which the distribution described in Formula 1 in the particles is adjusted can be prepared.

[0188] In the related art, the negative electrode active material is prepared by breaking a silicon block by physical force, and when the negative electrode active material is prepared as described above, the grain size is generally greater than 200 nm and the surface is smooth, so that the value of the specific surface area is less than 0.25 m 2 When the silicon-based active material is prepared simply by the method in the related art, the size of the specific surface area cannot be controlled, so there is a disadvantage that it is difficult to ensure the service life stability of the negative electrode.

[0189] However, the method for preparing negative electrode active materials according to the present application can form silicon particles by including the following steps: silane gasification of the silicon block through a chemical reaction under specific process conditions as described above, and then growing the silicon-based active material through crystal nucleation. Therefore, the method is characterized in that it can meet the specific surface area size and grain size according to the present application while controlling the grain direction.

[0190] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, the negative electrode for a lithium secondary battery comprising: a negative electrode collector layer; and a negative electrode active material layer formed on one surface or both surfaces of the negative electrode collector layer and comprising the negative electrode composition according to the present application or a cured product thereof.

[0191] Figure 1 1 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, it can be confirmed that the negative electrode for a lithium secondary battery 100 includes a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10. Figure 1 Although it is shown that the negative electrode active material layer is formed on one surface, the negative electrode current collector layer may include negative electrode active material layers on both surfaces.

[0192] In an exemplary embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by applying a negative electrode slurry including the negative electrode composition to one surface or both surfaces of the negative electrode collector layer and drying the negative electrode slurry.

[0193] In this case, the negative electrode slurry may include: the negative electrode composition described above; and a slurry solvent.

[0194] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy 5% or more and 40% or less.

[0195] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive, preferably 7% to 35% both inclusive, and more preferably 10% to 30% both inclusive.

[0196] The solid content of the negative electrode slurry may mean the content of the negative electrode composition contained in the negative electrode slurry, and may mean the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.

[0197] When the solid content of the negative electrode slurry satisfies the above range, viscosity is suitable during the formation of the negative electrode active material layer, and thus the present invention has a feature of being able to effectively form a negative electrode active material layer by minimizing the particle aggregation phenomenon of the negative electrode composition.

[0198] In an exemplary embodiment of the present application, the slurry solvent may be used without limitation as long as the slurry solvent can dissolve the negative electrode composition, and specifically, water or NMP may be used.

[0199] In an exemplary embodiment of the present application, the thickness of the negative electrode collector layer is generally 1 μm to 100 μm. There is no particular limitation on the negative electrode collector layer, as long as the negative electrode collector layer has high conductivity and does not cause chemical changes to the battery, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, materials having a surface treatment of the surface of copper or stainless steel with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloys, etc. can be used. In addition, the negative electrode collector layer can also increase the bonding strength of the negative electrode active material by forming fine concave-convex on its surface, and the negative electrode collector layer can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0200] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the thickness of the negative electrode collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.

[0201] However, the thickness may be variously modified depending on the type and purpose of the negative electrode used, and is not limited thereto.

[0202] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.

[0203] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.

[0204] The porosity varies depending on the composition and content of the silicon-based active material, conductive material and binder contained in the negative electrode active material layer. In particular, by containing the silicon-based active material and conductive material according to the present application in a specific composition and content, the above-mentioned range is satisfied, and therefore, it is characterized in that the conductivity and resistance in the electrode have an appropriate range.

[0205] In an exemplary embodiment of the present application, a lithium secondary battery is provided, the lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.

[0206] Figure 2 1 is a diagram showing a stacking structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, it can be confirmed that the negative electrode 100 for the lithium secondary battery includes a negative electrode active material layer 20 on one surface of the negative electrode collector layer 10, and it can be confirmed that the positive electrode 200 for the lithium secondary battery includes a positive electrode active material layer 40 on one surface of the positive electrode collector layer 50, and the negative electrode 100 for the lithium secondary battery and the positive electrode 200 for the lithium secondary battery are formed into a structure in which the electrodes are stacked with a separator 30 interposed therebetween.

[0207] A secondary battery according to an exemplary embodiment of the present specification may particularly include the above-mentioned negative electrode for a lithium secondary battery. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described in detail, its specific description will be omitted.

[0208] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.

[0209] In the positive electrode, there is no particular limitation on the positive electrode collector, as long as the positive electrode collector has conductivity without causing chemical changes to the battery, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 to 500 μm, and by forming fine concavoconvexities on the surface of the collector, the adhesion of the positive electrode active material can also be enhanced. For example, the positive electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0210] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material includes: a layered compound, such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or a compound replaced by one or more transition metals; a lithium iron oxide, such as LiFe3O4; a lithium manganese oxide, such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; 1-c2 M c2 Ni-site lithium nickel oxide represented by the chemical formula LiMn 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (herein, M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.6) or Li2Mn3MO8 (herein, M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4 in which a part of Li in the chemical formula is replaced by alkaline earth metal ions, etc., but is not limited thereto. The positive electrode may be Li metal.

[0211] In an exemplary embodiment of the present application, the positive electrode active material includes a lithium composite transition metal compound containing nickel (Ni), cobalt (Co) and manganese (Mn), and the lithium composite transition metal compound includes single particles or secondary particles, and the average particle size (D50) of the single particles can be greater than 1 μm.

[0212] For example, the average particle size (D50) of the single particles may be 1 μm to 12 μm, 1 μm to 8 μm, 1 μm to 6 μm, greater than 1 μm to 12 μm, greater than 1 μm to 8 μm, or greater than 1 μm to 6 μm.

[0213] Even if the single particle is formed into a small particle size with an average particle size (D50) of 1 μm or more and 12 μm or less, the particle strength can be excellent. 2 When the particle strength of the single particle is 100 to 300 MPa, the particle strength of the single particle can be 100 to 300 MPa. 2The strong rolling of the single particle also reduces the phenomenon of increasing the number of particles in the electrode due to particle breakage, thereby improving the service life characteristics of the battery.

[0214] The single particle may be prepared by mixing a transition metal precursor and a lithium raw material and firing the resulting mixture. The secondary particle may be prepared by a different method from the single particle, and its composition may be the same as or different from that of the single particle.

[0215] There is no particular limitation on the method for forming the single particles, but generally, the single particles can be formed by increasing the firing temperature to achieve overfiring, and the single particles can be prepared by using additives that facilitate overfiring such as grain growth promoters or by changing the starting material method.

[0216] For example, the firing is carried out at a temperature capable of forming a single particle. In order to form a single particle, the firing needs to be carried out at a temperature higher than the temperature at which the secondary particles are prepared. For example, when the composition of the precursor is the same, the firing needs to be carried out at a temperature about 30°C to 100°C higher than the temperature at which the secondary particles are prepared. The firing temperature for forming the single particle may vary depending on the metal composition in the precursor. For example, when it is desired to form a high Ni NCM lithium composite transition metal oxide having a nickel (Ni) content of 80 mol % or more as a single particle, the firing temperature may be 700°C to 1000°C, preferably about 800°C to 950°C. When the firing temperature satisfies the above range, a positive electrode active material comprising a single particle having excellent electrochemical performance can be obtained. When the firing temperature is lower than 790°C, a positive electrode active material comprising a lithium composite transition metal compound in the form of a secondary particle can be obtained. When the firing temperature exceeds 950°C, over-firing may occur, so that a layered crystal structure cannot be properly formed, thereby reducing the electrochemical performance.

[0217] In this specification, the single particle is a term used to distinguish a single particle from a secondary particle formed by the aggregation of tens to hundreds of primary particles in the related art, and is a concept that includes a single particle composed of one primary particle and a quasi-single particle that is an aggregate of 30 or less primary particles.

[0218] Specifically, in the present invention, the single particle may be in the form of a single particle composed of one primary particle or a quasi-single particle that is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of hundreds of primary particles.

[0219] In an exemplary embodiment of the present application, the lithium composite transition metal compound as a positive electrode active material further includes secondary particles, and the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.

[0220] In the present invention, the single particle may be in the form of a single particle composed of one primary particle or a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of hundreds of primary particles.

[0221] The lithium composite transition metal compound may further include secondary particles. The secondary particles are formed by aggregation of primary particles and can be distinguished from the concept of single particles including one primary particle, one single particle, or a quasi-single particle that is an aggregation of 30 or less primary particles.

[0222] The particle size (D50) of the secondary particles may be 1 μm to 20 μm, 2 μm to 17 μm, and preferably 3 μm to 15 μm. The specific surface area (BET) of the secondary particles may be 0.05 m 2 / g to 10 m 2 / g, preferably 0.1 m 2 / g to 1 m 2 / g, more preferably 0.3 m 2 / g to 0.8 m 2 / g.

[0223] In another exemplary embodiment of the present application, the secondary particles are aggregates of primary particles, and the average particle size (D50) of the primary particles is 0.5 μm to 3 μm. Specifically, the secondary particles may be in the form of aggregates of hundreds of primary particles, and the average particle size (D50) of the primary particles may be 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.

[0224] When the average particle size (D50) of the primary particles satisfies the above range, a single-particle positive electrode active material with excellent electrochemical performance can be formed. When the average particle size (D50) of the primary particles is too small, the number of primary particles that form lithium nickel oxide particles increases, so the effect of suppressing particle rupture during rolling is reduced. When the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles becomes longer, thereby increasing resistance and the output characteristics may deteriorate.

[0225] According to another exemplary embodiment of the present application, the average particle size (D50) of the single particle is characterized by being smaller than the average particle size (D50) of the secondary particle. Therefore, even if the single particle is formed with a small particle size, the single particle can have excellent particle strength, and the excellent particle strength can reduce the phenomenon of an increase in the number of particles in the electrode due to particle rupture, thereby improving the service life characteristics of the battery.

[0226] In an exemplary embodiment of the present application, an average particle diameter (D50) of the single particles is 1 μm to 18 μm smaller than an average particle diameter (D50) of the secondary particles.

[0227] For example, the average particle size (D50) of the single particles may be 1 μm to 16 μm, 1.5 μm to 15 μm, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.

[0228] When the average particle size (D50) of the single particle is smaller than the average particle size (D50) of the secondary particle, for example, when the above-mentioned range is met, the single particle can have excellent particle strength even if it is formed with a small particle size. Therefore, the excellent particle strength reduces the phenomenon of an increase in the number of particles in the electrode due to particle breakage, thereby improving the service life characteristics of the battery and improving the energy density.

[0229] According to another exemplary embodiment of the present application, based on 100 parts by weight of the positive electrode active material, the content of the single particle is 15 parts by weight to 100 parts by weight. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 20 parts by weight to 100 parts by weight, or 30 parts by weight to 100 parts by weight.

[0230] For example, based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 100 parts by weight or less.

[0231] When the single particles within the above range are included, the combination with the above negative electrode material can show excellent battery characteristics. In particular, when the amount of the single particles is 15 parts by weight or more, the phenomenon of increasing the number of particles in the electrode due to particle rupture during the rolling process after manufacturing the electrode can be reduced, thereby improving the service life characteristics of the battery.

[0232] In an exemplary embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the amount of the secondary particles may be 85 parts by weight or less based on 100 parts by weight of the positive electrode active material. Based on 100 parts by weight of the positive electrode active material, the amount of the secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less. Based on 100 parts by weight of the positive electrode active material, the amount of the secondary particles may be 0 parts by weight or more.

[0233] When the above range is met, the above effect caused by the presence of a single particle positive electrode active material can be maximized. When a secondary particle positive electrode active material is included, the composition may be the same as those exemplified in the above single particle positive electrode active material, or may be a different composition, and may mean a form in which a single particle form is aggregated.

[0234] In an exemplary embodiment of the present application, in 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0235] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.

[0236] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes to the constituted battery. Specific examples thereof include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used.

[0237] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples thereof may include: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.

[0238] The separator separates the negative electrode from the positive electrode and provides a channel for lithium ion movement, and can be used without particular restriction, as long as the separator is generally used as a separator in a secondary battery, in particular, preferably having excellent electrolyte moisture retention ability and having low resistance to ion movement in the electrolyte. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, a typical porous non-woven fabric can also be used, such as a non-woven fabric made of glass fiber, polyethylene terephthalate fiber, etc. with a high melting point. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.

[0239] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which can be used to prepare lithium secondary batteries, but are not limited thereto.

[0240] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0241] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate can be used.

[0242] In particular, among carbonate-based organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonates have high dielectric constants as high-viscosity organic solvents, thereby dissociating lithium salts well, and therefore can be preferably used, and the cyclic carbonates can be mixed with low-viscosity and low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate in an appropriate ratio to prepare an electrolyte with high conductivity, so such cyclic carbonates can be more preferably used.

[0243] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily dissolved in a non-aqueous electrolyte. For example, as the anion of the lithium salt, one or more selected from the group consisting of: F - , Cl -,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0244] In the electrolyte, in order to improve the service life characteristics of the battery, inhibit the decrease in battery capacity and improve the discharge capacity of the battery, on the basis of containing the above-mentioned electrolyte components, one or more additives may be included, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0245] An exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include secondary batteries having high capacity, high rate characteristics, and cycle characteristics, and thus can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0246] [Invention Mode]

[0247] Hereinafter, preferred embodiments will be proposed to facilitate the understanding of the present invention, but the embodiments are only provided to illustrate the present invention, and it should be obvious to those skilled in the art that various changes and modifications can be made within the scope and technical spirit of the present invention, and such changes and modifications naturally also fall within the appended claims.

[0248] <Preparation Example>

[0249] <Preparation of Negative Electrode Active Material of Example 1-5>

[0250] The active material was formed by chemically reacting silicon with silane gas to deposit silicon onto the nuclei in the reactor, and the growth time was adjusted as shown in Table 1 to produce the silicon-based active material. The range of the related I(220) / I(111) is shown in Table 1 below.

[0251] <Preparation of Negative Electrode Active Material of Comparative Example 1>

[0252] A silicon core installed in a metal reactor (reduction furnace) is resistively heated, and a gas in which the vapor of purified high-purity monosilane (SiH4) gas is mixed with purified hydrogen gas flows through the silicon core, thereby precipitating polycrystalline silicon on the surface of the silicon core, thereby preparing a polycrystalline silicon block manufactured in the form of a thick rod. Thereafter, a silicon-based active material is prepared by pulverization and classification.

[0253] <Preparation of Negative Electrode Active Material of Comparative Example 2>

[0254] The material is obtained in the same manner as in Example 1, except that the material obtained by growing silicon on a substrate instead of a crystal nucleus is crushed, and the material is deposited on the substrate in a state of flowing gas instead of in a reactor where the crystal nucleus is placed and made to flow.

[0255]

[0256] In Table 1 above, the spherical silicon-based active material refers to an active material having a roundness of 0.9 or more after measuring the roundness of each particle, and the weight parts of the spherical silicon-based active material refers to the weight parts in Table 1 based on 100 weight parts of the entire silicon-based active material.

[0257] <Preparation of negative electrode>

[0258] A negative electrode slurry was prepared by adding a negative electrode active material including a silicon-based active material, a first conductive material, a second conductive material and polyacrylamide as a binder in a weight ratio of 80:9.6:0.4:10 to distilled water as a negative electrode slurry forming solvent (solid concentration was 25 wt %).

[0259] Specifically, the first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is SWCNT.

[0260] As a specific mixing method, after the first conductive material, the second conductive material, the binder and water were dispersed at 2500 rpm for 30 minutes using a homomixer, a silicon-based active material was added thereto, and then the resulting mixture was dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.

[0261] The negative electrode slurry was prepared at 85 mg / 25 cm 2 The two surfaces of a copper current collector (thickness: 8 μm) as a negative electrode current collector layer were coated with a loading amount of, and the resulting product was rolled and dried in a vacuum oven at 130°C for 10 hours to form a negative electrode active material layer (thickness: 33 μm), which was used as a negative electrode (the thickness of the negative electrode: 41 μm, and the porosity of the negative electrode was 40.0%).

[0262] <Manufacturing of Secondary Battery>

[0263] By using LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black as a conductive material (product name: Super C65, manufacturer: Timcal Corporation) and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry in a weight ratio of 97:1.5:1.5 to prepare a positive electrode slurry (solid concentration is 78 wt %).

[0264] The positive electrode slurry was used at 537 mg / 25 cm 2 The two surfaces of an aluminum current collector (thickness: 12 μm) as a positive electrode current collector were coated with a loading amount of, and the resulting product was rolled and dried in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer (thickness: 65 μm), thereby preparing a positive electrode (the thickness of the positive electrode: 77 μm, the porosity is 26%).

[0265] A lithium secondary battery was prepared by interposing a polyethylene separator between the positive electrode and the negative electrode of each of Examples and Comparative Examples and injecting an electrolyte therein.

[0266] The electrolyte is obtained by adding 3 wt % of vinylene carbonate based on the total weight of the electrolyte to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) are mixed in a volume ratio of 10:90, and adding LiPF6 as a lithium salt at a concentration of 1 M thereto.

[0267] Experimental Example 1: Evaluation of the service life of a single battery

[0268] The secondary battery comprising the negative electrode manufactured in the embodiment and the comparative example was evaluated for service life using an electrochemical charger and discharger, and the capacity retention rate was evaluated. The secondary battery was subjected to an in-situ cycle test at 4.2-3.0V 1 C / 0.5 C, and the capacity retention rate was measured by charging / discharging the secondary battery at 0.33 C / 0.33 C (4.2-3.0 V) every 50 cycles during the test, and the results are shown in Table 2.

[0269] Lifespan retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the 1st cycle)} × 100

[0270]

[0271] Experimental Example 2: Evaluation of the discharge resistance increase rate (after 200 cycles) at SOC50 2.5 C

[0272] After measuring the capacity retention rate by charging / discharging the secondary battery at 0.33 C / 0.33 C (4.2-3.0 V) every 50 cycles during the test in Experimental Example 1, the resistance was measured by discharging the secondary battery at 2.5 C pulse at SOC50 to compare and analyze the resistance increase rate.

[0273] Regarding the evaluation of the resistance increase rate, data at 200 cycles were calculated for each test, and the results are shown in Table 3 below.

[0274]

[0275] As can be confirmed from the above Tables 2 and 3, it can be confirmed that in the case of Examples 1 to 5 in which the crystal plane according to the present application was adjusted, the service life evaluation and the resistance increase rate were excellent compared with Comparative Examples 1 and 2.

[0276] This is to control the distribution of grain directions that satisfies the range of the above formula 1, that is, when a relatively large proportion of (111) crystal planes are formed as in the related art, the lithium mobility of the (111) crystal planes is lower than that of the (220) crystal planes, so that lithium cannot be uniformly introduced during the lithium insertion / deinsertion reaction. However, it can be confirmed that, unlike the related art, the silicon-based active material according to the present application contains a large proportion of (220) crystal planes, so that lithium can be uniformly introduced during the lithium insertion / deinsertion reaction, thereby being able to reduce the silicon cracking phenomenon on the electrode surface, and accordingly, it is characterized by enhancing the service life characteristics of the electrode.

[0277] For reference, in the case of Comparative Example 1, it can be confirmed that the silicon core installed in the metal reactor (reduction furnace) is subjected to resistance heating, and a gas formed by a mixture of purified high-purity monosilane (SiH4) gas vapor and purified hydrogen gas flows through the silicon core, causing polycrystalline silicon to precipitate on the surface of the silicon core, and then the polycrystalline silicon is subjected to a crushing process. As a result, the value of Formula 1 (I(220) / I(111)×100) is relatively low, and therefore the service life evaluation and resistance increase rate evaluation are not as good as those in the embodiment.

[0278] Comparative Example 2 is a material obtained by crushing a material obtained by growing silicon on a substrate, and the material is deposited on the substrate in a state of flowing gas instead of in a reactor in which crystal nuclei are placed and flowed. Even in this case, as in Comparative Example 1, the value of Formula 1 is low, so it can be confirmed that the life evaluation and the resistance increase rate evaluation are not as good as those in the embodiment.

Claims

1. A negative electrode active material, the negative electrode active material comprising a silicon-based active material, the silicon-based active material comprising a (220) crystal plane and a (111) crystal plane, wherein the silicon-based active material satisfies the following Formula 1, the silicon-based active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 70 parts by weight or more: [Formula 1] 45 ≤ (X / Y) × 100 In Formula 1, Y means the proportion of the (111) crystal plane in the silicon-based active material, X means the proportion of the (220) crystal plane in the silicon-based active material.

2. The negative electrode active material according to claim 1, wherein the silicon-based active material comprises one or more selected from the group consisting of spherical silicon-based active materials and plate-shaped silicon-based active materials, and based on 100 parts by weight of the silicon-based active material, the content of the spherical silicon-based active material is 80 parts by weight or more.

3. The negative electrode active material according to claim 1, wherein the D50 particle size of the silicon-based active material is 3 μm or more and 10 μm or less.

4. The negative electrode active material according to claim 1, wherein the grain size of the silicon-based active material is 200 nm or less.

5. A method for preparing the negative electrode active material according to any one of claims 1 to 4, the method comprising: depositing a silicon-based active material onto the surface of a crystal nucleus by subjecting a silane gas to a chemical reaction; and obtaining the silicon-based active material deposited on the surface of the crystal nucleus, wherein the silicon-based active material satisfies the following Formula 1: [Formula 1] 45 ≤ (X / Y) × 100 In Formula 1, Y means the proportion of the (111) crystal plane in the silicon-based active material, X means the proportion of the (220) crystal plane in the silicon-based active material.

6. The method according to claim 5, wherein the silane gas comprises one or more gases selected from the group consisting of monosilane, dichlorosilane, and trichlorosilane.

7. The method according to claim 5, wherein the depositing of the silicon-based active material onto the surface of the crystal nucleus by subjecting the silane gas to a chemical reaction is carried out under high-temperature conditions of 100°C or more.

8. The method according to claim 5, further comprising: Depositing a silicon-based active material onto the surface of a crystal nucleus by subjecting a silane gas to a chemical reaction; subsequently growing the silicon-based active material by crystal nucleation, wherein the growing of the silicon-based active material by crystal nucleation includes generating crystal nuclei at a temperature of 800°C or more for 1 hour to 24 hours.

9. A negative electrode composition, the negative electrode composition comprising: the negative electrode active material according to any one of claims 1 to 4; a negative electrode conductive material; and a negative electrode binder.

10. The negative electrode composition according to claim 9, wherein based on 100 parts by weight of the negative electrode composition, the content of the negative electrode active material is 60 parts by weight or more. 11 . The negative electrode composition according to claim 9 , wherein the negative electrode conductive material comprises one or more selected from the group consisting of a point conductive material, a surface conductive material, and a line conductive material.

12. A negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: a negative electrode current collector layer; and A negative electrode active material layer is provided on one surface or both surfaces of the negative electrode current collector layer, The negative electrode active material layer comprises the negative electrode composition according to claim 9 or a cured product thereof.

13. The negative electrode according to claim 12, wherein the thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and The thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.

14. A lithium secondary battery, comprising: positive electrode; The negative electrode for a lithium secondary battery according to claim 12; A separator disposed between the positive electrode and the negative electrode; and Electrolytes.

Citation Information

Patent Citations

  • Anode for lithium ion battery

    JP2009080971A

  • Manufacturing method for anti-inflammation composition using tartary buckwheat

    KR1020220110078A